2017
DOI: 10.7554/elife.22268
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neurosensory progenitor pools during inner ear morphogenesis unveiled by cell lineage reconstruction

Abstract: Reconstructing the lineage of cells is central to understanding how the wide diversity of cell types develops. Here, we provide the neurosensory lineage reconstruction of a complex sensory organ, the inner ear, by imaging zebrafish embryos in vivo over an extended timespan, combining cell tracing and cell fate marker expression over time. We deliver the first dynamic map of early neuronal and sensory progenitor pools in the whole otic vesicle. It highlights the remodeling of the neuronal progenitor domain upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…We sought to determine how size control is achieved in the zebrafish otic vesicle, a 3D lumenized epithelial cyst that becomes the inner ear. Prior studies used qualitative observations and 4D imaging to examine the formation of the otic vesicle (Haddon and Lewis, 1996; Hoijman et al, 2015; Dyballa et al, 2017). To systematically investigate inner ear morphogenesis at longer timescales between 12–45 hours post-fertilization (hpf), we used high-resolution 3D+ t confocal imaging combined with automated algorithms for quantifying cell and tissue morphology (Figure 1—figure supplement 1A–F) (Megason, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We sought to determine how size control is achieved in the zebrafish otic vesicle, a 3D lumenized epithelial cyst that becomes the inner ear. Prior studies used qualitative observations and 4D imaging to examine the formation of the otic vesicle (Haddon and Lewis, 1996; Hoijman et al, 2015; Dyballa et al, 2017). To systematically investigate inner ear morphogenesis at longer timescales between 12–45 hours post-fertilization (hpf), we used high-resolution 3D+ t confocal imaging combined with automated algorithms for quantifying cell and tissue morphology (Figure 1—figure supplement 1A–F) (Megason, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of hair cell innervation of afferents along the mediolateral axis of the ganglion suggested a possible link between developmental sequence and connectivity. In the vestibular ganglion, early born afferents occupy the most lateral edge of the nascent ganglion (Dyballa et al, 2017;Vemaraju et al, 2012;Zecca et al, 2015). Later-born afferents are added more medially, forming a half-shell around the earliest born somata.…”
Section: Organization Of the Utricular Ganglion By Developmental Sequencementioning
confidence: 99%
“…Thirdly, neuronal connectivity could be conferred retrogradely from the oculomotor neuron pools, which are segregated spatially during development (Greaney et al, 2016), as has been suggested for the chick (Glover, 1996) and shown for spinal interneurons (Baek et al, 2017). Finally, temporal cues could guide fate decisions: recent in vivo timelapse imaging demonstrated how peripheral afferents develop systematically in time (Zecca et al, 2015; Dyballa et al, 2017). Similar organization by birthdate has been demonstrated in extraocular motoneurons (Greaney et al, 2016) and spinal motor circuits (McLean and Fetcho, 2009) using genetically-encoded photoconvertible markers of post-mitotic neurons.…”
Section: Open Questions Well-suited To the Zebrafish Modelmentioning
confidence: 99%